ANALISIS EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN PAJAK DAERAH SEBELUM DAN SESUDAH PENERAPAN SISTEM TAPPING BOX DALAM UPAYA MENGOPTIMALKAN PENDAPATAN ASLI DAERAH (PAD) KOTA TANJUNGPINANG - fauzi; satria, hendy; alamsyahbana, muhammad isa; chandra saputra, novi (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
Abstract: The purpose of this study was to analyze the effectiveness and contribution of local tax revenues before and after the application of the tapping box system in an effort to optimize the local revenue (pad) of the city of Tanjung Pinang. This type of research is descriptive qualitative, the type of data used in this study is secondary data. The data collection technique is done by using interviews, documentation, observation and literature study. The data analysis technique uses effectiveness analysis and contribution analysis. From the results of this study, it can be concluded that the level of effectiveness of hotel tax receipts, restaurant taxes, and entertainment invites before the application of the tapping box system in 2016-2017 shows very effective criteria and after the application of the tapping box system in 2018-2019 shows very effective criteria. for hotel tax in 2016 it was 101.27%, in 2017 it was 108.26%, in 2018 it was 103.22%, and in 2019 it was 100.00%. for restaurant tax in 2016 it was 119.40%, in 2017 it was 111.43%, in 2018 it was 105.46%, and in 2019 it was 112.26%. for entertainment tax in 2016 it was 118.53%, in 2017 it was 108.70%, in 2018 it was 104.11%, and in 2019 it was 100.27%.